2023
DOI: 10.1021/acs.jafc.2c07207
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Chlorophyll and Other Isoprenoids in the Plastid of Red Grape Berry Skins

Abstract: Despite current knowledge showing that fruits like tomato and grape berries accumulate different components of the light reactions and Calvin cycle, the role of green tissues in fruits is not yet fully understood. In mature tomato fruits, chlorophylls are degraded and replaced by carotenoids through the conversion of chloroplasts in chromoplasts, while in red grape berries, chloroplasts persist at maturity and chlorophylls are masked by anthocyanins. To study isoprenoid and lipid metabolism in grape skin chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…'Albert Lavallée' [41], and cv. 'Vinhao' [25]. Interestingly, at the ripening stage, we found that the relative amount of γ-tocopherol was slightly higher than α-tocopherol (Figure 1D), displaying an opposite accumulation, as described for several table grape and wine grape cultivars [42].…”
Section: Lipid Profiling Of Grape Bunches During Flowering and Berry ...supporting
confidence: 52%
See 2 more Smart Citations
“…'Albert Lavallée' [41], and cv. 'Vinhao' [25]. Interestingly, at the ripening stage, we found that the relative amount of γ-tocopherol was slightly higher than α-tocopherol (Figure 1D), displaying an opposite accumulation, as described for several table grape and wine grape cultivars [42].…”
Section: Lipid Profiling Of Grape Bunches During Flowering and Berry ...supporting
confidence: 52%
“…Stigmasterol abundance decreased during grape berry ripening, as previ-ously reported for cv. 'Vinhao' [25]. Furthermore, grapevine genotype is not the only component influencing lipid profile.…”
Section: Lipid Profiling Of Grape Bunches During Flowering and Berry ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Non-polar (NP) and semi polar (SP) metabolites were extracted from, respectively, 3 and 10 mg of freeze-dried tomatoes, harvested at the red stage, for a total of three replicates for each of the seven SSL and the seven LSL genotypes. Liquid chromatography coupled to high-resolution mass spectrometry (HPLC-APCI/ESI-HRMS) conditions were as previously reported for NP ( Teixeira et al., 2023 ) and SP ( Dono et al., 2022 ) metabolome, respectively. Metabolites were identified through the comparison with authentic standards or MS/MS spectra when available and on the basis of the accurate masses obtained from the Pubchem database ( http://pubchem.ncbi.nlm.nih.gov/ ) for native compounds or from the Metabolomics Fiehn Lab Mass Spectrometry Adduct Calculator ( http://fiehnlab.ucdavis.edu/staff/kind/Metabolomics/MS-Adduct-Calculator/ ) for adducts.…”
Section: Methodsmentioning
confidence: 99%
“…Of all natural pigments, chlorophylls, belonging to the porphyrins, are the most common pigments on Earth. Chlorophylls are light-harvesting pigments that are widely distributed in plants, algae, and cyanobacteria, and they can be used in pharmaceutical and cosmetic industries. Carotenoids, belonging to the isoprenoids, are also important industrial pigments; their global market may reach 2 billion USD by 2027 . As a result of the excellent antioxidant properties of carotenoids, they are used commercially in the food, feed, cosmetic, and pharmaceutical fields .…”
Section: Introductionmentioning
confidence: 99%